Forensic art essentials : a manual for law enforcement artists - Gibson, Lois (Academic Press, 2008)
The demand for forensic art usage in investigations is rapidly expanding due to media attention. Despite this fact, to date no book thoroughly explains how to sketch a suspect's face from a witness memory. Forensic Art Essentials teaches artists to extract information from a witness or victim about a face they have seen, and produce an image good enough to lead detectives to the criminal being described. After reading this book, anyone with adequate drawing skills will be able to learn the tools necessary to develop his or her skills as a forensic artist. Instruction focuses on an explanation of techniques for various scenarios and includes the use of case studies of special situations and how they should be handled. Additionally, Forensic Art Essentials covers skull reconstructions of unidentified murder victims and age progressions to aid in the apprehension of known fugitives. The book also provides step-by-step illustrations of how to reconstruct a face from a skull, and offers solutions to a multitude of common problems that occur in the field. With 500 full-color illustrations, this book is an essential tool for any forensic artist. * Provides insight as to the best way to responsibly interview and extract information from eye-witnesses and victims to develop accurate composite sketches * 500 illustrations, many full color, show examples of various challenges in developing sketches and reconstructing from skulls * Serves as a guide for forensic art professionals as well as a call to law enforcement agencies to expand the use of this valuable forensic tool.